Labor force participation of married women in Turkey: Is there an added or a discouraged worker effect? - Deniz Karaoglan; Cagla Okten (Institute for the Study of Labor (IZA), 2012)
This article analyzes married women's labor supply responses to their husbands' job loss (added worker effect) and worsening of unemployment conditions (discouraged worker effect). We find that married women whose husbands are unemployed or underemployed are more likely to participate in the labor force and work more hours using yearly cross-sectional data from Turkey for the 2000-2010 period. We also construct two year panels based on questions on previous year's labor market outcomes. Panel results provide further support for the added worker effect. Wives whose husbands experience a job loss are more likely to increase their labor force participation. However, a worsening of overall unemployment conditions appears to have a discouraging effect on wives' labor supply response, wives tend to decrease their labor participation when unemployment rate in their region increases.
Keywords: J21; J60; 330; female labor force participation; added worker effect; Turkey; Weibliche Arbeitskräfte; Erwerbstätigkeit; Ehe; Männer; Arbeitslosigkeit; Türkei